The consumer journey on collaborative consumption platforms : an empirical study using structure equation modeling - Tomar, Shailendra Singh (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research e CRM